Vertebral Fracture in Postmenopausal Women with and without Osteoporosis - Merih Özgen (Türk Osteoporoz Dergisi, 2017)
Objective: Osteoporosis (OP) is a major cause of disability, morbidity and mortaliy. Causes are significant economic burden with fractures. Dual energy X-ray absorptiometry (DXA) is the only technique that is defined as the gold standard that the World Health Organization currently recommends in determining the fracture risk. The use of direct radiographic examinations is recommended for the causes of false negative results in densitometric examination and for the detection of fracture presenting as OP indicator in clinical practice. The purpose of this study is a retrospective investigation of the need for DXA methodology, which we routinely use for diagnosis, treatment and follow-up of OP, in patients with fractures by direct radiography. Materials and Methods: The data of 189 postmenopausal women with DXA, lateral thoracic and lumbar graphy without trauma history, retrospectively evaluated. Patients were divided into two groups according to DXA results, group 1 consisted 167 postmenopausal women with OP and group 2 consisted 22 postmenopausal women with no OP. In both groups, patients who have at least one fracture according to thoracic and lumbar graphy were evaluated. Results: At least one vertebrae height loss was detected in 61 (32.28%) of 189 postmenopausal women included in the study. At least one fracture was detected in 49 (29.34%) of 167 patients with OP according to DXA results and 12 (54.55%) of 22 patients without OP. Conclusion: With this study; retrospectively demonstrated the need for follow-up of patients with fractures by direct radiography in conjunction with DXA, the gold standard for OP diagnosis and treatment planning in postmenopausal women.